Assessing the probiotic potential, antioxidant, and antibacterial activities of oat and soy milk fermented with Lactiplantibacillus plantarum strains isolated from Tibetan Kefir - Aziz, Tariq; Xingyu, Hu; Sarwar, Abid; Naveed, Muhammad; Shabbir, Muhammad Aqib; Khan, Ayaz Ali; Ulhaq, Taqweem; Shahzad, Muhammad; Zhennai, Yang; Shami, Ashwag; Sameeh, Manal Y.; Alshareef, Sahar A.; et al. (Frontiers in Microbiology, 2023)
Sufficient intake of probiotics has been shown to help in the digestion, protect the body against pathogenic microorganisms and boost the immune system. Recently, due to high prevalence of milk allergies and lactose intolerance in population, the non-dairy based probiotic alternative are becoming increasing popular. In this context, the oat milk and soya milk-based fermented products can be an ideal alternative for the development of Lactic acid bacteria bacteria based probiotics. These bacteria can not only improve the product's flavor and bioavailability but also increases its antibacterial and antioxidant capabilities due to fermentation process. The purpose of the resent work was to assess the antioxidant and probiotic properties of oat and soy milk that had been fermented with three different strains of Lactiplantibacillus plantarum (L. plantarum) inclusing L. plantarum 12-3, L. plantarum K25, and L. plantarum YW11 isolated from Tibetan Kefir. Different validated assays were used to evaluate the probiotic properties, adhesion and survival in the digestive system (stomach, acid and bile salts resistance), antioxidant and antimicrobial activities and safety (ABTS and DPPH scavenging assays) of these strains. Results of the study showed that soya milk and oat milk fermented with L. plantarum strains possess promising probiotic, antibacterial and antioxidant properties. These results can be helpful to produce dairy-free probiotic replacements, which are beneficial for those who are unable to consume dairy products due to dietary or allergic restrictions.